THE INFLUENCE OF WORK DISCIPLINE AND SITUATIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT SMO IN BATAM - Atmaja, Agus Sekti Susila; Sumarya, Edi; Nuraeni, Brigida Endah (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This research is entitled "The Influence of Work Discipline and Situational Leadership Style on Employee Performance at PT SMO in Batam City". With the aim of examining the influence of work discipline and situational leadership style on the performance of PT SMO employees. Research data was obtained through questionnaires and studied based on theories obtained from literature study. The method in this research uses quantitative research techniques. The population and sample determined were PT SMO employees with a total of 62 respondents. The research results show that individually, the significance value of work discipline of 0.000 is smaller than α = 0.05 so it is decided that it has a significant effect on employee performance. Situational leadership style does not have a significant effect on employee performance. The significance value of situational leadership style is 0.810 greater than α = 0.05. Based on the Beta value, it is known that the variable that has the dominant influence on employee performance is work discipline at 0.762 (76.2%). Together, work discipline and situational leadership style have a significant effect on the performance of PT SMO employees. This decision is based on the significance level of the F value of 41.166 with a significance level of 0.000 which is smaller than α = 0.05. Keywords: Work Discipline, Situational Leadership Style, Employee Performance.